Barnabas: A leadership model for the Nigerian society - Adewale, Olubiyi A. (HTS teologiese studies, 2021)
It has usually been accepted that the success of any organisation or nation depends on the ability of its leader to govern and manage its affairs. The failure of most developing countries, especially Nigeria, has often been blamed on bad leadership. Most Nigerians are of the opinion that the leadership problem in Nigeria has been the major impediment in the nation’s development. Most people also agree that corruption and bad governance, which are prevalent in Nigeria today, are the results of leadership failure. The consensus among scholars, critics and observers of the Nigerian state is that the current situation of the nation is the result of lack of good and purposeful leadership. It is because of leadership failure in the country that Nigerians today clamor for good and purposeful leadership. This paper is a contribution to the search for the long-awaited leader. This paper examines Barnabas’ character using the narrative method.Contribution: This article reveals that Barnabas was a bridge-builder, team player, non-discriminatory and not power or position drunk and these are the traits that should be used as a model in selecting or electing leaders within ecclesiastical and secular circles.